National Identity And Its Appearance In The Poetry Of The Liberation Revolution -algerian Poets As A Model- - khemis, Ridha (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : Identity represents the reality of the nation and its essential attributes, and given what Algeria suffered under French colonialism during a century and a half of practices that distorted and distorted this identity, the Algerian people and its elites, including the Association of Algerians Muslim scholars, were on the lookout for this colonial stratagem to distort the Algerian human personality, which is why our intervention comes Tagged: National identity and its manifestations in the poetry of the liberation revolution - given that poetry is the diwan of the Arabs, to which they entrust with the secrets of their civilizational dimension -, and if literature and poetry in particular are based on the activation of the spirit of originality and national identity and on resisting the challenges that beset the self through his continuous struggle at the turning points of time, then The Algerian revolutionary poet sought to give this struggle an image through which he embodies the idea of affirmation of herself in the midst of what she suffers from alienation which threatens her identity and makes her lose the authenticity of her civilized belonging. memory, in which we will adopt the descriptive and analytical approach.